Bottom-up versus Top-down Campaigning at the Scottish Independence Referendum 2014 - Peter Lynch (Revue Française de Civilisation Britannique)
The Scottish independence referendum of 2014 saw one of the longest political campaigns in modern UK politics. The referendum saw the formation of a hybrid Yes campaign that combined modern campaigning techniques with a large, activist grassroots that established a range of new political organisations. Not only did these organisations continue to develop after the referendum itself, but they contributed to the formation of a broad social movement in favour of independence for the first time in Scotland.